Cyclophosphamide‐based stem cell mobilization in relapsed multiple myeloma patients: A subgroup analysis from the phase III trial ReLApsE. (24th May 2017) - Baertsch, Marc‐Andrea; Schlenzka, Jana; Lisenko, Katharina; Krzykalla, Julia; Becker, Natalia; Weisel, Katja; Noppeney, Richard; Martin, Hans; Lindemann, Hans W.; Haenel, Mathias; Nogai, Axel; Scheid, Christof; et al.
Abstract: Objective: Analysis of the efficiency and toxicity of cyclophosphamide‐based stem cell mobilization in patients with relapsed multiple myeloma (RMM). Methods: Peripheral blood stem cells (PBSCs) were mobilized with high dose cyclophosphamide (2 g/m 2 daily on days 1 and 2) and G‐CSF plus pre‐emptive/rescue plerixafor in RMM patients (first to third relapse) treated within the ReLApsE trial of the German‐Speaking Myeloma Multicenter Group (GMMG). Results: Mobilization was initiated with high‐dose cyclophosphamide (HD‐CY) and G‐CSF in 30 patients. Fifteen patients received additional pre‐emptive/rescue administration of plerixafor. Stem cell collection was successful (≥2×10 6 CD34+ cells per kg bw) in 77% (23/30 patients). Patients with prior high‐dose melphalan collected a significantly lower median total number of PBSCs than patients without prior high‐dose melphalan (3.3×10 6 vs 17×10 6 CD34+ cells/kg bw). Toxicity of HD‐CY was frequent with 12 serious adverse events (SAE) in 37% of patients (11/30 patients). Infections accounted for the majority of SAE reports. In two patients, SAEs were lethal (septic shock). Conclusions: These data proof feasibility of PBSC collection at relapse but emphasize the importance of collection and storage of additional PBSC transplants during first‐line treatment when mobilization is more efficient and less toxic.